Armanni–Ebstein Lesions: A Need for Clarification. (12th September 2012) - Zhou, Chong; Yool, Andrea J.; Nolan, James; Byard, Roger W.
Abstract: Armanni–Ebstein lesions were first described by Luciano Armanni, a pathologist at the University of Naples, during autopsy studies undertaken in 1872, as a unique vacuolar nephropathy associated with poorly controlled diabetes that involves selective renal epithelial cell glycogen accumulation. However, within the last two decades, a broader range of vacuolar changes, including lipid deposition, have also been termed Armanni–Ebstein (AE) lesions, creating some confusion on possible etiology. We would suggest that the term AE phenomenon would be best reserved for the original clear cell change associated with glycogen deposition, and that this should be clearly distinguished from subnuclear lipid vacuolization ("basal vacuolization"). Although there is obvious inter‐relation between these two types of vacuoles, they appear morphologically and biochemically distinct from each other. More precise classification may assist in clarifying the causal processes and possible diagnostic significance of different types of renal epithelial vacuolization at autopsy.